An Ecosocial Reading of Slow Violence in Latife Tekin’s Manves City - Özlem Akyol (Selçuk Üniversitesi Edebiyat Fakültesi Dergisi)
Ecocriticism is an increasingly heterogeneous movement under which a variety of approaches fall. One of these approaches is Ecosocialism which expands the critical scope towards environmentally serious social issues within cities. The theory combines revolutionary and green perspectives to promote equality and living in harmony with nature in a classless society. At this point, Rob Nixon’s innovative concept ‘slow violence’ of which effects are not immediate but dispersed time and space has been frequently associated with Ecosocialism. Through ecosocial lenses, slow violence can be considered as a common threat for environment and society since the theory perceives both as cheap resources gradually exploited for profit. The environmental and social effects of such violence strikingly appear in Latife Tekin’s Manves City1 (2018) in which a post-industrial small town and its inhabitants’ tragic lives are portrayed. Based on Tekin’s socialist and green perspectives which are frequently adopted in her literary works, Manves City, in which exploitative attitude of employers towards nature and workers and the gradual extinction of nature in parallel with the degradation in domestic life of local people are discussed as essential themes, lends itself Ecosocial criticism. In analyzing the novel through ecosocial lenses, the paper also aims to reveal the interacting relation between environmental and social degradation through Tekin’s depiction of slow violence.